InSAR observations of strain accumulation and fault creep along the Chaman Fault system, Pakistan and Afghanistan. Issue 16 (18th August 2016) - Fattahi, Heresh; Amelung, Falk
Abstract: We use 2004–2011 Envisat synthetic aperture radar imagery and InSAR time series methods to estimate the contemporary rates of strain accumulation in the Chaman Fault system in Pakistan and Afghanistan. At 29 N we find long‐term slip rates of 16 ± 2.3 mm/yr for the Ghazaband Fault and of 8 ± 3.1 mm/yr for the Chaman Fault. This makes the Ghazaband Fault one of the most hazardous faults of the plate boundary zone. We further identify a 340 km long segment displaying aseismic surface creep along the Chaman Fault, with maximum surface creep rate of 8.1 ± 2 mm/yr. The observation that the Chaman Fault accommodates only 30% of the relative plate motion between India and Eurasia implies that the remainder is accommodated south and east of the Katawaz block microplate. Key Points: Chaman Fault accommodates only 30% of the relative plate motion between India and Eurasia A 340 km creeping segment of Chaman Fault with maximum surface creep rate of 8 mm/yr identified with InSAR Ghazaband Fault is locked accumulating strain with a rate of 16 mm/yr